Board-management relationships: Resources and internal dynamics - Ljiljana Erakovic; Sanjay Goel (Management Revue, 2008)
This paper investigates directors' relationships with firms' managers, using lenses of resource dependence theory and resource based view. Because of different roles that board members perform in modern organisations we seek to find out what boardmanagement relationships may provide a company with competitive advantage relative to other firms. The paper reports the results from a study conducted in six New Zealand companies. We used multiple respondents from the top management and board members in a variety of firms from different industries. Qualitative analysis of interview transcripts, and matching the qualitative results with secondary information on the companies, reveal several interesting patterns of relationship among top management and board members, as well as the value of this relationship to the firm.
Keywords: 650; corporate governance; board-management dynamics; resource dependence; resource-based view